2022
DOI: 10.1186/s13195-022-01079-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alzheimer’s disease polygenic risk scores with amyloid accumulation in cognitively intact older adults

Abstract: Background Early detection of individuals at risk for Alzheimer’s disease (AD) is highly important. Amyloid accumulation is an early pathological AD event, but the genetic association with known AD risk variants beyond the APOE4 effect is largely unknown. We investigated the association between different AD polygenic risk scores (PRS) and amyloid accumulation in the Flemish Prevent AD Cohort KU Leuven (F-PACK). Methods We calculated PRS with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(85 reference statements)
2
3
1
Order By: Relevance
“…These findings suggest that other genetic variants, independent of APOE, may play a role in modulating the risk of AD and potentially compensate for or complement the effect of APOE in genetic predisposition to the disease. Our results align with previous studies, 41,42 emphasizing the importance of considering additional APOE-independent mechanisms when exploring genetic predisposition to AD. This illustrates how the use of PRS can reveal additional pathophysiological pathways with potential for prevention, 43 which is relevant since the pathophysiology of AD has not yet been fully elucidated and the best biological characterization to date focuses on the determination of AD biomarkers.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that other genetic variants, independent of APOE, may play a role in modulating the risk of AD and potentially compensate for or complement the effect of APOE in genetic predisposition to the disease. Our results align with previous studies, 41,42 emphasizing the importance of considering additional APOE-independent mechanisms when exploring genetic predisposition to AD. This illustrates how the use of PRS can reveal additional pathophysiological pathways with potential for prevention, 43 which is relevant since the pathophysiology of AD has not yet been fully elucidated and the best biological characterization to date focuses on the determination of AD biomarkers.…”
Section: Discussionsupporting
confidence: 92%
“…The study also revealed an increased genetic predisposition to AD in ALFA participants, even in the absence of the APOE-4 allele. This suggests that other variants (APOEindependent mechanisms) associated with AD appear to compensate for or complement the effect of APOE in genetic predisposition to AD, which is consistent with other studies (Luckett et al, 2022;Skoog et al, 2021). This illustrates how the use of PRS can reveal additional pathophysiological pathways with potential for prevention.…”
Section: Discussion and Future Directionssupporting
confidence: 88%
“…Accumulation of amyloid-β protein in the brain is characteristic of Alzheimer’s disease and can occur many years before the onset of symptoms (Luckett et al 2022). As a prominent example, APOE , the largest genetic risk factor for AD, has been associated with amyloid-β accumulation in the brain, therefore identifying genetic risk variants prior to symptom onset is critical for treatment decisions and potential enrollment in prevention trials.…”
Section: Discussionmentioning
confidence: 99%